GLOTTODYDAKTYCZNE OBSZARY BADAŃ NAD KOMPETENCJĄ MIĘDZYKULTUROWĄ - Róg, Tomasz (Neofilolog, 2018)
As globalisation promotes cross-cultural approaches to foreign language education, the article scrutinises research on intercultural competence conducted in the field of glottodidactics. It aims at offering a possibly most comprehensive outline of our state-of-the-art knowledge of interculturality in teaching foreign languages. The following parts of the present article will look at pre- and in-service teachers, teaching materials, lesson planning, new technologies, and the age of learners, all with a view to indicating the achievements and challenges of teaching intercultural competence as an element of foreign language education.